Use of Spinal Anesthesia in Lower Thoracic Spine Surgery: A Case Series. Issue 4 (6th October 2022) - Wang, Andy Y.; Liu, Penny; Balonov, Konstantin; Riesenburger, Ron; Kryzanski, James
Abstract : BACKGROUND: Spinal anesthesia is a safe and effective alternative to general anesthesia for patients undergoing lumbar spine surgery, and numerous reports have demonstrated its advantages. To the best of our knowledge, no group has specifically reported on the use of spinal anesthesia in thoracic-level spine surgeries because there is a hypothetical risk of injuring the conus medullaris at these levels. With the advantages of spinal anesthesia and the desire for many elderly patients to avoid general anesthesia, our group has uniquely explored the use of this modality on select patients with thoracic pathology requiring surgical intervention. OBJECTIVE: To investigate the feasibility of performing thoracic-level spinal surgeries under spinal anesthesia and report our experience with 3 patients. METHODS: A retrospective chart review of medical records was undertaken, involving clinical notes, operative notes, and anesthesia records. RESULTS: Three spinal stenosis patients underwent thoracic laminectomy under spinal anesthesia. Two surgeries were performed at the T11-T12 level and 1 at the T12-L1 level. The average age was 82 years, average American Society of Anesthesiologists score was 3.3, and 1 identified as female. Two cases used hyperbaric 0.75% bupivacaine dissolved in dextrose, and 1 used isobaric 0.5% bupivacaine dissolved in water. CONCLUSION: Spinal anesthesia is feasible for thoracic-level spine procedures, even in elderly patients with comorbidities. We describe our cases and technique for safely achieving a thoracic level of analgesia, as well as discuss recommendations, adverse events, and considerations for the use of spinal anesthesia during lower thoracic-level spine operations.